IRoSim: Industrial Robotics Simulation Design Planning and Optimization platform based on CAD and knowledgeware technologies - Baizid, Khelifa; Ćuković, Saša; Iqbal, Jamshed; Yousnadj, Ali; Chellali, Ryad; Meddahi, Amal; Devedžić, Goran; Ghionea, Ionut (Robotics and computer-integrated manufacturing, 2016)
This paper presents Industrial Robotics Simulation Design Planning and Optimization platform named IRoSim, which is based on SolidWorks Application Programming Interface (API) to offer an intuitive and convertible environment for designing and simulating robotized tasks. The core idea is to integrate features of mechanical CAD and robotics CAD into the same platform to facilitate the development process through the designed Graphical User Interface (GUI) which permits user friendly interaction. The platform includes various 3D models that are essential for developing any robotized task and offers possibility to integrate new models in simulation. Robotic manipulator library is one such example which contains several types of serial arms with different combinations of revolute and prismatic joints. The platform provides most important steps such as defining the task, CAD learning of the end-effector's trajectory, checking the manipulator's reachability to perform a task, simulating the motion and finally validating the manipulator's trajectory to avoid possible collisions. To demonstrate the efficiency of the proposed approach, two frequent and important tasks (spot welding and painting) using a 6-Degree Of Freedom (DOF) industrial robotic manipulator have been considered. The output of the proposed strategy provides collision-free trajectory of the manipulator's motion which can be directly mapped to a real site. Moreover, the approach permits addressing the problems related with the real implementation of robotized tasks. •A CAD robotic platform named IRoSim for simulation of robotized tasks is presented.•The platform offers CAD learning trajectory and time optimization based on GA.•Task definition, accessibility verification and collision avoidance are considered.•The proposed platform works as plug-in with SolidWorks based on VBA.•Case studies of spot welding and painting demonstrate potential of the platform.